Performance Analysis of Bit-Error-Rate and Channel Capacity of MIMO Communication Systems over Multipath Fading Channels - Isiaka Ajewale Alimi; Jide Julius Popoola; Kayode Francis Akingbade; Michael O. Kolawole (Institute of Advanced Engineering and Science, 2013)
In wireless communication systems (WCS), channel characteristics are random and unpredictable. The resultant effect of the randomness is the multipath effect that leads to multipath fading. Multipath fading is a major contributor to the unreliability of wireless communication links. In this paper, Multiple-Input, Multiple-Output (MIMO) schemes were investigated in mitigating the effect of signal fading. Space-time coded MIMO-OFDM was developed to enhance the performance of the WCS. The performance of the developed space-time coded MIMO-OFDM over both flat and frequency selective channels were compared with that of conventional WCS. The simulation results show that the space-time coded MIMO-OFDM considerably reduced the effect of multipath fading in WCS with improved bit error rate (BER) value.DOI: http://dx.doi.org/10.11591/ij-ict.v2i2.2014